Silver nitrate and adenine sulphate induced high regeneration frequency in the recalcitrant plant Cosmos bipinnatus using cotyledon explants. Issue 2 (4th March 2018) - Jaberi, Mahdi; Azadi, Pejman; Gharehyazi, Behzad; Khosrowchahli, Mahmood; Sharafi, Ali; Aboofazeli, Nafiseh; Bagheri, Hedayat
ABSTRACT: Plant regeneration ability was studied in the medicinal-ornamental plant, Cosmos bipinnatus 'Sonata white', which is a dicotyledonous recalcitrant plant to shoot induction. Cotyledons were used as sources of explants to investigate plant regeneration. High frequency of direct shoot induction was obtained when BA (5 mg/l) and AgNO3 (5 mg/l) were used in combination with 20 mg/l adenine sulphate (73.8%) in Murashige and Skoog (MS) medium. The highest shoot number per explant (5.7) was induced on MS medium supplemented with 5 mg/l BA, 5 mg/l AgNO3, and 40 mg/l adenine. Eight week-old shoots were transferred to root induction media containing MS and half-strength MS medium with different concentration of IBA. The highest rate of root induction (70.8%) was obtained on half-strength MS medium with 1.5 mg/l IBA within four weeks. The plantlets were transferred to pot and kept in the greenhouse condition. Seventy percent of the plantlets successfully acclimatised. Abbreviations: BA, 6-benzylaminopurine; IBA, Indole-3-butyric acid; MS, Murashige and Skoog; PGRs, plant growth regulators.